Al-Âyah al-Mutasyâbihât al-Lafzhiyyah fi Sûrah al-An’âm ‘Inda al-Kirmâny - Hikmatiar Pasya; Muhammad Iqbal Rivai (Studia Quranika, 2017)
This paper discusses about the verses of mutasyâbihât in the Quran. The debate of this versescaused various opinions. The meaning of the mutasyâbihât in this paper is the similarity and difference of the words in the Qur'an. Mufasir have different opinion about the meaning of the verse of mutasyâbihât al-lafdzi. In addition, many Hufadz of the Quran who are confused from one verse to another, or one chapter to another. It’s because similarity of verses in the Qur'an with other verses. So the writer wants to explain the verses mutasyâbihât al-lafdzi in the perspective of Hamzh al-Karmani in Surah al-An'âm. In this discussion the author discovers some passages in mutasyâbihât al-lafdzi, namely asrâru al-balaghah fi mutasyabih al-lafdzi, asrar al-balaghah fi mutasyabih al-hurf, and murâ'ah al-ikhtilâf murâd bi al-lafdzi al-mukarrar.